2020
DOI: 10.1038/s41598-020-66666-7
|View full text |Cite
|
Sign up to set email alerts
|

Low molecular weight silicones induce cell death in cultured cells

Abstract: Women with silicone gel-filled breast implants are exposed to organosilicon compounds, in particular methylsiloxanes, as a result of 'gel bleed' and implant rupture. Although these silicones were originally considered to be inert, increasing evidence indicates that they can cause serious health problems. Here, we have analyzed the effects of microdroplets of the methylcyclosiloxanes, in particular D4, on the viability of cultured human cells. The exposure of Jurkat suspension and HeLa monolayer cells to D4 res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…In our study, the bright green fluorescence with different proportion was observed in the cells in both liquid and emulsified LMWC groups, indicating that the apoptotic process was involved in the ARPE-19 cell death pathway after LMWC treatment. This is consistent with the results of another in vitro study in which D4 induced the death of Jurkat cells with several apoptotic processes including the cleavage of caspase-3 and DNA fragmentation [ 36 ]. However, the underlying mechanism of cell death induced by LMWC exposure still requires further long-term experiments to confirm.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the bright green fluorescence with different proportion was observed in the cells in both liquid and emulsified LMWC groups, indicating that the apoptotic process was involved in the ARPE-19 cell death pathway after LMWC treatment. This is consistent with the results of another in vitro study in which D4 induced the death of Jurkat cells with several apoptotic processes including the cleavage of caspase-3 and DNA fragmentation [ 36 ]. However, the underlying mechanism of cell death induced by LMWC exposure still requires further long-term experiments to confirm.…”
Section: Discussionsupporting
confidence: 92%
“…In HeLa cells (cervical carcinoma epithelial cells), toxicity was less efficient, whereas in HEp-2 cells (human epithelial cells), cell death was not observed. 36 The results presented in the article suggest that in addition to the mechanism proposed by our theory, the direct toxicity of silicone in T cells and eventually on epithelial cells in the TME could catalyze the process of oncogenesis.…”
Section: Discussionmentioning
confidence: 67%
“…In this context, in a recent study, Onneking et al described the possible cellular toxicity exerted by silicone. 36 According to the authors, silicone implants are composed of cross-linked alloys of polydimethylsiloxane chains in three-dimensional networks. Since the chains are cross-linked, lower molecular weight silicone particles with linear or cyclic structures, including D4, D5, and D6, filled the empty spaces.…”
Section: Discussionmentioning
confidence: 99%
“…This was well evidenced by a post-mortem analysis of tissues sampled from a patient with a 17-year-history of gel bleed after receiving a silicone gel-filled breast implant. The patient was characterized by the presence of plaques or droplets containing silicones in several organs and nervous tissue [118]. Over the past decades, the involvement of a silicone gel-filled breast implant in the pathophysiology of autoimmune inflammatory disorders.…”
Section: Discussionmentioning
confidence: 99%